Tariffs, time preference, and the current account under weakly nonseparable preferences - Shinsuke Ikeda (Osaka University, Institute of Social and Economic Research (ISER), 2000)
Incorporating weakly nonseparable preferences into the familiar time-preference model, we emphasize a role of steady-state welfare changes in determining the effect of permanent tariffs on the current account. The effect consists of: a welfare effect, due to steady-state welfare changes, which is negative (positive) when preferences toward imports are more (less) wealth-enhanced than toward exports; and a substitution effect, which occurs only with initial distortion. Even without initial distortion, a marginal tariff has a first-order welfare effect on the current-account. Its sign does not depend on whether impatience is increasing or decreasing in wealth.
Keywords: F41; F32; F13; 330; time preference; weakly nonseparable preferences; current account; Zollpolitik; Zeitpräferenz; Leistungsbilanz; Präferenztheorie; Neoklassisches Wachstumsmodell; Wohlfahrtsanalyse; Theorie